THE SIGNIFICANCE OF ABBREVIATIONS IN GEOGRAPHICAL TERMINOLOGY (World Bulletin of Social Sciences, 2026)
The essential reason for using abbreviations in geography is efficiency. On a physical map, there isnt enough space to write Mountain Range or Administrative District next to every name. Furthermore in the age of Digital Mapping and GIS abbreviations help in data processing and standardization. Instead of writing Mountain Hissar cartographers prefer to write Mt. Hissar